Preparation of activated carbon from durian rind with difference activations and its optimization - Sriprom, Pongsert; Krusong, Warawut; Assawasaengrat, Pornsawan (My University, 2021)
Durian rind wastes are an important raw material for activated carbon production due to their renewable sources and low-cost materials. The efficiency of increasing surface area and the quantity of oxygen groups on the surface of activated carbon were studied for the preparation of activated carbon. The preparation of activated carbon has been studied with the different methods as follows: activation by acid, activation by base, hydrothermal and activation by acid, and hydrothermal and activation by base. The results showed that hydrothermal and activation by acid had high iodine number which was chosen to determine the optimum condition for activated carbon preparation. The optimum condition for preparation of durian rind activated carbon was studied by Box-Behnken design. Solid/water ratio, solid/acid ratio and temperature were chosen as the important parameters for achieving the optimum reaction condition. The reaction products were analyzed by iodine number. Based on the results, the optimum condition for preparation of durian rind activated carbon was predicted using RSM. The maximum iodine number of 626.47 mg/g was expected at the optimum condition: solid/ water ratio (1:175, g/mL), solid/acid ratio (1:23, g/mL) and temperature (500°C). The preparation of durian rind activated carbon at the optimal condition was carried; the percentages of iodine number achieved (666.73 ± 6 mg/g) were close to the maximum predicted value (666.73 mg/g), thus verifying the model. At the optimum condition, the functional group on surface of durian rind activated carbon was characterized by FT-IR. The result showed that the oxygen content on surface was increased in the form of carbonyl and sulfonyl group.
Keywords: Activated carbon; Durian rind; Hydrothermal; Iodine number